On the Demographic Policy in the European Socialist Countries - Merčaitis, Antanas (Problemos, 1973)
The paper deals with general regularities of the natural population movement in the European socialist countries. It is shown that the rate of natural increase in population during the post-war period has considerably decreased. Among the many reasons of this phenomenon, a reduction in woman’s productivity figures prominently. The author discusses the effects and prospects of productivity and the aging of population. Prominence is given mainly to the analyses of measures taken in separate countries to raise the rate of birth.